World Aquaculture: Environmental Impacts and Troubleshooting Alternatives - Marcel Martinez-Porchas; Luis R. Martinez-Cordova (The Scientific World Journal)
Aquaculture has been considered as an option to cope with the world food demand. However, criticisms have arisen around aquaculture, most of them related to the destruction of ecosystems such as mangrove forest to construct aquaculture farms, as well as the environmental impacts of the effluents on the receiving ecosystems. The inherent benefits of aquaculture such as massive food production and economical profits have led the scientific community to seek for diverse strategies to minimize the negative impacts, rather than just prohibiting the activity. Aquaculture is a possible panacea, but at present is also responsible for diverse problems related with the environmental health; however the new strategies proposed during the last decade have proven that it is possible to achieve a sustainable aquaculture, but such strategies should be supported and proclaimed by the different federal environmental agencies from all countries. Additionally there is an urgent need to improve legislation and regulation for aquaculture. Only under such scenario, aquaculture will be a sustainable practice.